The molecular basis of hypertrophic scars. Issue 1 (December 2016) - Zhu, Zhensen; Ding, Jie; Tredget, Edward
Abstract Hypertrophic scars (HTS) are caused by dermal injuries such as trauma and burns to the deep dermis, which are red, raised, itchy and painful. They can cause cosmetic disfigurement or contractures if craniofacial areas or mobile region of the skin are affected. Abnormal wound healing with more extracellular matrix deposition than degradation will result in HTS formation. This review will introduce the physiology of wound healing, dermal HTS formation, treatment and difference with keloids in the skin, and it also review the current advance of molecular basis of HTS including the involvement of cytokines, growth factors, and macrophages via chemokine pathway, to bring insights for future prevention and treatment of HTS.